'Education comes second to surviving': parental perspectives on their child/ren's early school leaving in an area challenged by marginalisation. Issue 1 (2nd January 2019) - Doyle, Gavin; Keane, Elaine
Abstract : This paper examines early school leaving from the perspective of parents of early school leavers in an inner-city local authority housing estate in the Republic of Ireland living with the challenges of significant marginalisation. While the vast majority of post-primary pupils now sit a Leaving Certificate examination, and improvements in school retention rates have also been found in 'disadvantaged' schools in recent years, a disproportionate number of those leaving school early come from lower socio-economic backgrounds. Through in-depth, semi-structured, interviews, this qualitative study examined the perspectives of nine parents of early school leavers about the factors contributing to young people from this area leaving school early. This article focuses on three aspects of the findings through which the parent participants framed their views on early school leaving; (1) feeling let down by school, and (2) being stigmatised being from a 'disadvantaged' area, and (3) dealing with life traumas. For the participants, these factors significantly constrained their child/ren in engaging with education. The findings are examined through an interrogation of the shaping impact of social class and 'place'. Recommendations include specific professional development for educators in challenging contexts about the impact of trauma and socio-demographical positionality on educational engagement and outcomes.